Characterization and simulation of the response of Multi-Pixel Photon Counters to low light levels - Vacheret, A; Barker, G; Dziewiecki, M; Guzowski, P; Haigh, M; Hartfiel, B; Izmaylov, A; Johnston, W; Khabibullin, M; Khotjantsev, A; Kudenko, Y; Kurjata, R; et al. (2011)
The calorimeter, range detector and active target elements of the T2K near detectors rely on the Hamamatsu Photonics Multi-Pixel Photon Counters (MPPCs) to detect scintillation light produced by charged particles. Detailed measurements of the MPPC gain, afterpulsing, crosstalk, dark noise, and photon detection efficiency for low light levels are reported. In order to account for the impact of the MPPC behavior on T2K physics observables, a simulation program has been developed based on these measurements. The simulation is used to predict the energy resolution of the detector. Copyright © 2011 Published by Elsevier B.V. All rights reserved.